THE PHYTOCHEMICAL AND PHARMACOLOGICAL PROPERTIES OF SARPAGANDHA: RAUWOLFIA SERPENTINA - Malviya, *Anshu; Sason, Rajveer (AYUSHDHARA, 2016)
Sarpagandha, Rauwolfia serpentina is a medicinal plant explained in Ayurvedic literature and in modern science. The plant is known for curing various disorders because of the presence of alkaloids, carbohydrates, flavonoids, glycosides, phlobatannins, phenols, resins, saponins sterols, tannins and terpenes. The plant parts, root and rhizome have been used since centuries in Ayurvedic medicines for curing a large number of diseases such as high blood pressure, mental agitation, epilepsy, traumas, anxiety, excitement, schizophrenia, sedative insomnia and insanity This review represents brief information about botanical description, chemical constituents, and functional as well as medicinal uses of Rauwolfia serpentina. In past years it was declared as a best remedy for hypertension. The alkaloid found in its root is attributed to anti hypertensive pharmacological action. In Ayurvedic literature too Our Acharyas has defined various remarkable properties like its Jwarhar, Varnanashak, Grahi, Nidrajanan, Svashahar, Soolprashamna prabhav of this plant. The plant also has number of pharmaceutical applications i.e. may be used as excipient in many of formulations. There is a need for us to search alternative, naturally available remedies for curing millions of people worldwide. Due to all these properties, the present review aims to evaluate the various pharmacological, phytochemical and therapeutic properties of R. serpentine.